Las raíces de los géneros periodísticos interpretativos: precedentes históricos formales del reportaje y la entrevista. - Díaz Noci, Javier (Estudios sobre el Mensaje Periodístico, 2000)
The characteristics usually thought to be of informative and interpretative texts (especially report and interview) are not to be exclusively found in these kind of journalistic genres. Those genres, on one hand, are often ascribed to English-language tradition, and some others, like chronicle, on the other hand, are considered Latin genres. In this article some similar techniques used in reports and interviews and in some Middle-Ages and Renaissance anglo-germanic literary and legal texts are shown.